Ten years of experience with intravesical and intrasphincteric onabotulinumtoxinA in children. Issue 2 (April 2016) - Greer, T.; Abbott, J.; Breytenbach, W.; McGuane, D.; Barker, A.; Khosa, J.; Samnakay, N.
Summary: Objective: To review 10 years of experience with both intravesical and intrasphincteric onabotulinumtoxinA (Botox ® ) injections in children. Patients and methods: Fifty three children aged between 1 and 18 years at first injection had a combined total of 134 injections (106 intravesical, 23 intrasphincteric and five combined) between January 2004 and December 2013 at Princess Margaret Hospital. Follow-up occurred 3 months post procedure, and then 3–6 monthly. Response to Botox was graded according to the International Children's Continence Society (ICCS) response to treatment scale. Response time was the time that the injection remained effective before symptoms relapsed to the ICCS 'no response' category Nevéus et al., 2006. Results: Median response times to Botox by pathology are summarised in Table 1. For detrusor overactivity (DO), the response after each Botox injection was in the ICCS '>90% symptom reduction' category Nevéus et al., 2006. Two children had sustained responses to Botox for a tenth and eleventh injection, respectively. A total of 45% of children receiving intrasphincteric Botox for chronic dysfunctional voiding (DV) or detrusor sphincter dyssynergia (DSD) had no symptom recurrence. Intravesical Botox was effective for treating new-onset hydronephrosis secondary to neurogenic bladder in one child. Intravesical Botox had a sustained effect over five injections in eliminating trigonal hypersensitivity and pain with CIC in one child. Episodes of severe autonomic dysreflexia in one child with a high cord transection were effectively eliminated by intravesical Botox, and were sustained over three injections. Thirteen of the 134 Botox injections (9.7%) had a symptomatic culture-positive urinary tract infection (UTI) in the 2 weeks following injection. All had a history of previous UTI. Three children (2.8%) developed urinary retention after intravesical injection. Discussion: Intravesical Botox remained effective after up to eleven injections. In children with DV or DSD, the response to Botox was more variable, but 45% experienced symptom resolution with no recurrence. Trigonal hypersensitivity with CIC improved in a child after Botox. Botox may confer long-term bladder and upper tract protection in the neurogenic patient group. Severe episodes of autonomic dysreflexia triggered by bladder fill in a child with high cord lesion were eliminated by intravesical Botox. Conclusion: This study demonstrated that intravesical Botox remained effective in response quality and response time in children up to an eleventh injection. This is one of the longer follow-up studies in children published to date. Botox was effective in numbing trigonal hypersensitivity, treating new-onset hydronephrosis secondary to neurogenic bladder, and eliminating episodes of autonomic dysreflexia in one patient each. Table Median response time of Botox injections by pathology. Pathology Number of children Median response time (months) Range (months) Neurogenic detrusor overactivity (NDO) 22 7 0–25 Idiopathic detrusor overactivity (IDO) 15 5.25 0–15 Dysfunctional voiding 6 3.5 0–12 Detrusor sphincter dyssynergia 5 4 0–10 Acute urinary retention 5 0 0–3 New-onset hydronephrosis in NDO a 1 8 – Trigonal hypersensitivity b 1 4 2.5–5 Autonomic dysreflexia a 1 7 5–7 a Child also had underlying NDO. b Child also had underlying IDO.